2010
DOI: 10.1089/jwh.2009.1357
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Student Gender on the Obstetrics and Gynecology Clerkship Experience

Abstract: Male students were more likely to experience gender bias from patients on the obstetrics and gynecology service. Male students also described feeling socially excluded from female-dominated clinical teams. Obstetrics and gynecology educators need to consider methods of encouraging patients to accept medical student participation regardless of gender. Obstetrics and gynecology faculty and residents need to be sensitive to subtle forms of gender bias and ensure equal inclusion for both male and female medical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 24 publications
4
75
1
Order By: Relevance
“…Next, respondents were asked about their attitudes toward students and the possible reasons for their acceptance or refusal of student involvement in the whole clinic process, including history taking and intimate/pelvic examination. As there were different acceptance rates for male and female medical students in previous studies, 1,[14][15][16][17][18] this part was designed to ask patients about their attitudes toward involving four specific groups of medical students in consultations and pelvic or obstetrical examinations: Chinese female (CF), International female (IF), Chinese male (CM), and International male (IM). They were asked to rate their acceptance level on a 5-point ordinal scale (1 ¼ strongly agree, 2 ¼ agree, 3 ¼ neutral, 4 ¼ disagree, and 5 ¼ strongly disagree).…”
Section: Questionnaire Design and Study Variablesmentioning
confidence: 99%
“…Next, respondents were asked about their attitudes toward students and the possible reasons for their acceptance or refusal of student involvement in the whole clinic process, including history taking and intimate/pelvic examination. As there were different acceptance rates for male and female medical students in previous studies, 1,[14][15][16][17][18] this part was designed to ask patients about their attitudes toward involving four specific groups of medical students in consultations and pelvic or obstetrical examinations: Chinese female (CF), International female (IF), Chinese male (CM), and International male (IM). They were asked to rate their acceptance level on a 5-point ordinal scale (1 ¼ strongly agree, 2 ¼ agree, 3 ¼ neutral, 4 ¼ disagree, and 5 ¼ strongly disagree).…”
Section: Questionnaire Design and Study Variablesmentioning
confidence: 99%
“…This quality medical education is especially important given projected shortages of OB-GYN providers in upcoming years (Chang et al, 2010b;Higham, 2006). Hands-on experience with patients is a key component of this education.…”
Section: Relationship Of Literature To the Current Studymentioning
confidence: 99%
“…Numerous studies have shown that male students are more likely to be refused than female students. 3,[7][8][9][10][11][12] Though many studies have evaluated the rate of medical student refusal and reasons for refusal, few studies have been published regarding interventions to decrease rates of medical student refusal. 13 The frequency of refusal among students and reasons for refusal had not previously been investigated at the University of Iowa.…”
Section: Introductionmentioning
confidence: 99%